The Relationship Between Upward Propagating Atmospheric Gravity Waves and Ionospheric Irregularities During Solar Minimum Periods - Ephrem B. Seba; Melessew Nigussie; Nigussie M. Giday; Mark B. Moldwin (Space Weather)
Abstract We present a study on the relationship between upward propagating gravity waves and ionospheric irregularities. Gravity waves (GWs) are identified from Thermosphere Ionosphere Mesosphere Energetics and Dynamics (TIMED) satellite temperature measurements and nighttime ionospheric irregularities are observed from the three Swarm satellites. Using these two independent set of measurements, we investigate the relationship between gravity waves and ionospheric irregularities on both equinox and solstice seasons for the years 2018–2019. The results show, post‐sunset gravity wave characteristics are important in understanding the variability of global nighttime equatorial plasma density irregularities. We also find out that the pre‐midnight and post‐midnight characteristics of ionospheric irregularities show global westward shift in the occurrence of ionospheric irregularities. Upward propagating gravity waves also show three dominant peaks longitudinally with the strongest being between American and African longitudinal sectors. Strongest gravity wave amplitudes are associated with strongest plasma irregularities. GW suppression is observed around equatorial regions at stratopause region in our measurements which are commonly observed at polar and higher latitudinal regions in many studies. We also observe that, ionospheric irregularities are strongest when GWs are relatively less suppressed.